Indonesian defense diplomacy through Confidence-Building Measure (CBM) in Southeast Asia - Minardi, Anton; Yusro, M. Rizky (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indonesian Defense Diplomacy through Confidence Building Measures (CBM) in Southeast Asia is a defense diplomacy step taken by Indonesia towards countries in Southeast Asia. So, the aim of this research is to find out the Confidence-Building Measures (CBMs) that Indonesia has built between international relations actors in the Southeast Asia region using three views of CBMs according to Glosserman, namely unilateral, bilateral and multilateral actions aimed at reducing and preventing war conflicts between parties to the conflict. This research uses a description method with qualitative analysis. As a result, Indonesia has taken important steps to build trust and reduce tensions in the region. Through various peaceful means such as military dialogue, exchange of security information, joint military exercises and multilateral diplomacy, Indonesia seeks to avoid conflict escalation and build mutually beneficial cooperation. In the framework of building CBM, Indonesia faces several conditions that influence the choice of CBM measures, such as prolonged disputes, threats of hostility, incentives to attack first, and disproportionate war costs. The importance of defense diplomacy and cooperation in the Southeast Asia region is reflected in Indonesia's participation in various regional frameworks such as the ASEAN Regional Forum (ARF), ASEAN Defense Ministers' Meeting (ADMM), and Shangri-La Dialogue. Indonesia seeks to build trust through dialogue, information exchange and joint military activities.